Une formulation symétrique pour le couplage éléments finis-éléments de frontière en mécanique - Mouhoubi, Saïda; Ulmet, Laurent; Bonnet, Marc (European Journal of Computational Mechanics, 2002)
This article presents a formulation for the symmetrical coupling of finite element and boundary element methods, based on the symmetric Galerkin boundary integral equations for three-dimensional elasticity, in regularized form. The stiffness matrix of an elastic region is, as a result, expressed in terms of the boundary displacement DOFs. Its extension to elastic regions containing cracks is also presented. The procedure has been implemented in the FEM-based environment CAST3M. Three numerical examples are shown: a pressurized spherical cavity in an infinite elastic-plastic medium, an assembly structure, and a cracked cylindrical bar.